HUBUNGAN NEUTROFIL LIMFOSIT RASIO DENGAN LAMA RAWAT INAP PADA PASIEN SEPSIS AKIBAT PNEUMONIA PADA TAHUN 2019-2020 DI ICU RSUD H. AMRI TAMBUNAN - DINA YASMIN NASUTION; IRFAN HAMDANI (LP2MTBM MAKARIOZ, 2023)
Sepsis due to bacterial infection in the blood is a serious medical emergency that requires prompt and appropriate treatment. Worsening of this condition can lead to septic shock, which is characterized by severe circulatory and/or metabolic abnormalities, and can lead to death. Pneumonia is the most common cause of sepsis in many reported case reports. NLR can be used as a screening for septic patients because it has better sensitivity and accuracy but is confirmed by blood culture as the standard. The association of organ dysfunction with mortality and high mortality rates in septic patients and the increasing costs in the ICU indicate the need to predict the length of stay of patients to provide information to patients and their families related to the patient's disease prognosis. This prompted this study to find out the relationship between neutrophil lymphocyte ratio and length of stay in patients with sepsis due to pneumonia. This study aims to determine the relationship between neutrophil lymphocyte ratio and length of stay in patients with sepsis due to pneumonia in 2019-2020 in the ICU of Drs. H. Amri Tambunan Deli Serdang. This study used a descriptive analytic method with a cross sectional design. The data was processed using SPSS Chi-Square. The result showed that the relationship between neutrophil lymphocyte ratio and length of stay in patients with sepsis due to pneumonia in 2019-2020 in the ICU of RSUD Drs. H. Amri Tambunan Deli Serdang showed a p-value of 0.0051 (p<0.05). There is a significant relationship between the neutrophil lymphocyte ratio and length of stay in patients with sepsis due to pneumonia in 2019-2020 in the ICU of RSUD Drs. H. Amri Tambunan Deli Serdang